Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's solve the problem step-by-step. We are given two functions [tex]\( f(x) = 16x - 30 \)[/tex] and [tex]\( g(x) = 14x - 6 \)[/tex]. We need to find the value of [tex]\( x \)[/tex] for which [tex]\( (f - g)(x) = 0 \)[/tex].
1. Define the combined function [tex]\( (f - g)(x) \)[/tex]:
\[tex]\[ (f - g)(x) = f(x) - g(x) \\][/tex]
2. Substitute the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] into the combined function:
\[tex]\[ (f - g)(x) = (16x - 30) - (14x - 6) \\][/tex]
3. Simplify the expression:
\[tex]\[ (f - g)(x) = 16x - 30 - 14x + 6 \\][/tex]
Combine like terms:
\[tex]\[ (f - g)(x) = (16x - 14x) + (-30 + 6) \\][/tex]
\[tex]\[ (f - g)(x) = 2x - 24 \\][/tex]
4. Set the combined function equal to 0:
\[tex]\[ 2x - 24 = 0 \\][/tex]
5. Solve for [tex]\( x \)[/tex]:
Add 24 to both sides of the equation:
\[tex]\[ 2x - 24 + 24 = 0 + 24 \\][/tex]
\[tex]\[ 2x = 24 \\][/tex]
Now, divide both sides by 2:
\[tex]\[ x = \frac{24}{2} \\][/tex]
\[tex]\[ x = 12 \\][/tex]
Therefore, the value of [tex]\( x \)[/tex] for which [tex]\( (f - g)(x) = 0 \)[/tex] is:
\[tex]\[ \boxed{12} \\][/tex]
1. Define the combined function [tex]\( (f - g)(x) \)[/tex]:
\[tex]\[ (f - g)(x) = f(x) - g(x) \\][/tex]
2. Substitute the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] into the combined function:
\[tex]\[ (f - g)(x) = (16x - 30) - (14x - 6) \\][/tex]
3. Simplify the expression:
\[tex]\[ (f - g)(x) = 16x - 30 - 14x + 6 \\][/tex]
Combine like terms:
\[tex]\[ (f - g)(x) = (16x - 14x) + (-30 + 6) \\][/tex]
\[tex]\[ (f - g)(x) = 2x - 24 \\][/tex]
4. Set the combined function equal to 0:
\[tex]\[ 2x - 24 = 0 \\][/tex]
5. Solve for [tex]\( x \)[/tex]:
Add 24 to both sides of the equation:
\[tex]\[ 2x - 24 + 24 = 0 + 24 \\][/tex]
\[tex]\[ 2x = 24 \\][/tex]
Now, divide both sides by 2:
\[tex]\[ x = \frac{24}{2} \\][/tex]
\[tex]\[ x = 12 \\][/tex]
Therefore, the value of [tex]\( x \)[/tex] for which [tex]\( (f - g)(x) = 0 \)[/tex] is:
\[tex]\[ \boxed{12} \\][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.